Initial Experience Using the New pHLO 0.072-inch Large-Bore Catheter for Direct Aspiration Thrombectomy in Acute Ischemic Stroke - Giuseppe Leone; Massimo Muto; Flavio Giordano; Gianluigi Guarnieri; Antonio Di Donna; Camilla Russo; Daniele Giuseppe Romano; Paolo Candelaresi; Giovanna Servillo; Emanuele Spina; Antonio De Mase; Vincenzo Andreone; et al. (Neurointervention, 2023)
Purpose A direct aspiration, first pass technique (ADAPT) has been introduced as a rapid and safe thrombectomy strategy in patients with intracranial large vessel occlusion (LVO). The aim of the study is to determine the technical feasibility, safety, and functional outcome of ADAPT using the newly released large bore pHLO 0.072-inch aspiration catheter (AC; Phenox). Materials and Methods We performed a retrospective analysis of data collected prospectively (October 2019–November 2021) from 2 comprehensive stroke centers. Accessibility of the thrombus, vascular recanalization, time to recanalization, and procedure-related complications were evaluated. National Institutes of Health stroke scale scores at presentation and discharge and the modified Rankin scale (mRS) score at 90 days post-procedure were recorded. Results Twenty-five patients (14 female, 11 male) with occlusions of the anterior circulation were treated. In 84% of cases, ADAPT led to successful recanalization with a median procedure time of 28 minutes. In the remaining cases, successful recanalization required (to a total of 96%; modified thrombolysis in cerebral infarction score 2b/3) the use of stent retrievers. No AC-related complications were reported. Other complications included distal migration of the thrombus, requiring a stent-retriever, and symptomatic PH2 hemorrhage in 16% and 4%, respectively. After 3 months, 52% of the patients had mRS scores of 0–2 with an overall mortality rate of 20%. Conclusion Results from our retrospective case series revealed that thrombectomy of LVOs with pHLO AC is safe and effective in cases of large-vessel ischemic stroke. Rates of complete or near-complete recanalization after the first pass with this method might be used as a new benchmark in future trials.